Development of an Experimental Facility for Measurement of Tangential Jet Flow in a Sudden Expansion Channel - Abd Rahim, Irfan (2006)
This thesis describes the development of an experimental facility of a tangential jet flow in a sudden expansion channel. The present study is intended to clarify experimentally the relation between flow and geometrical variables on the thermal development using a point wise temperature measurements technique. The temperature measurements have been conducted on a flat plate inside a low speed open circuit wind tunnel. The mainstream flow has a maximum of temperature 50" C. The temperature was controlled by a 10 kVA/40 Ampere voltage regulator. A maximum velocity, (urnat) t he mainstream intake is 10 d s . The velocity on the coolant jet flow (u,)is between 2 m/s to 8 mls, the expansion ratio (ER) is 1.2 and the Reynolds numbers, ( ~ e , ) is, 1.3 x 1 o5 on the mainstream location. The coolant distribution system is fabricated into three type of geometry: a slot shape 20 mm2 1 mm , a square shape 10 mm x 10 rnm and a circular shape 10 mm of diameter. The surface temperature in the direction of the jet flow media is evaluated based on the measured temperatures, obtained through the thermocouples over the flat surfaces. The jet flow is tangentially injecting a jet of cooling air at an exit angle of 0" from the coolant distribution system to the plate surface. The test plate is made of plastic material (acrylonitrile butadiene stryrene) plate of 10 mm thick flat plate which is installed on the channel wall and instrumented with a stream wise row of Ttype thermocouples. The thermocouples are spaced 25.4 mm apart along the center line of the plate. The temperature ratio between the cooling air temperature (T,) and T the mainstream temperature (T,) is in the range of 0.77 5 1 0.87 while the T, velocity ratio between the cooling velocity (u,)an d mainstream velocity (u,) is in range of 0.2 5 35 0.7. From the observation made at the location XX -- 0.5, the cooling effectiveness (r) for tangential jet flow emanating from the slot, square and circular holes geometry, is to be at maximum value of 0.8, 0.6, and 0.5 respectively. The data presented here would be off interest to engineers to gain further understanding in the development of heat transfer due to tangential jet flow in a sudden expansion channel.